(untitled) (Revista Geoaraguaia, 2021)
Molla Taleb pegmatites (northeast of Aligudarz) are located in the western part of the metamorphic-igneous Sanandaj-Sirjan Zone (SSZ). Slates and schists along with siliceous veins and veinlet and black Hornfels, as well as metamorphic sandstones are among the oldest deposits of this area. The most important geological event in this area is the development and intrusion of granitoid masses into schists of the Molla Taleb area during the Middle Jurassic. The rocks of the study area are in the range of gabbro, diorite, granodiorite, and granite. Granites are in the range of type-I granites. Most specimens are calc-alkaline and mainly contain peraluminous. Microprobe electron analysis of tourmalines present in pegmatites, tourmaline- aplite-pegmatite veins, nodular tourmalines, and quartz-tourmaline veins shows that all tourmalines are in the Schorl region and the range of alkaline tourmalines. These tourmalines with FeO / FeO + MgO ratios between 0.6 and 0.8 are in the range of magmatic-hydrothermal tourmalines and more than 0.8 in the magmatic range. Therefore, the studied tourmalines are dependent on granite environments and are formed by a hydrothermal fluid of magmatic origin.